2015
DOI: 10.1002/joc.4543
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characteristics of hourly precipitation over central eastern China during the warm season of 1982–2012

Abstract: An intensive observational hourly precipitation data set from the China Meteorological Administration was utilized to investigate the changes in precipitation amount, frequency, intensity and duration over central eastern China during the warm season from 1982 to 2012. Ten intensity categories were used to reveal the contributions of precipitation frequency and intensity to the variation of rainfall amount. Moreover, the trends of frequency were also evaluated by comparing the respective contributions of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 79 publications
3
30
1
Order By: Relevance
“…As reported by Kaiser (), eigenvalue separations were used to test the number of region divisions, and their corresponding maximum loading vectors were used to determine the climate divisions. A total of ten spatial patterns were determined over central eastern China, with their accumulated variance contribution exceeding 60% (Li et al , ). The rainy area over South China can be well represented by the second leading mode of the REOF analysis (Figure (b)) which contributes 7.84% to the total variation of precipitation over China.…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Kaiser (), eigenvalue separations were used to test the number of region divisions, and their corresponding maximum loading vectors were used to determine the climate divisions. A total of ten spatial patterns were determined over central eastern China, with their accumulated variance contribution exceeding 60% (Li et al , ). The rainy area over South China can be well represented by the second leading mode of the REOF analysis (Figure (b)) which contributes 7.84% to the total variation of precipitation over China.…”
Section: Resultsmentioning
confidence: 99%
“…In general, a significant increase was observed in both hours of precipitation and frequency of precipitation events at most stations in the north of the Poyang Lake Basin, and a significant increase in heavy precipitation at some stations in eastern parts of the central region. Compared with other regions in China (Yu et al 2011;Zhang et al 2011;Yang et al 2013;Wen et al 2015;Li et al 2016), the growth rate of the frequency of heavy precipitation events has been faster in the Poyang Lake Basin, particularly at some stations in eastern parts of the central region. Given this very strong signal, the risk of extreme precipitation disasters in this region is increasing considerably.…”
Section: Discussionmentioning
confidence: 87%
“…However, in northeastern China and the Sichuan Basin, the precipitation amount in each precipitation intensity category has shown a declining trend (Zhai et al 2005;Yao et al 2008;. Seasonally, precipitation has increased during winter and summer but decreased during spring and autumn (Huang and Wen 2013;Wen et al 2015;Li et al 2016). The variation of extreme precipitation over large river basins in China has also been studied (Zhai et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Dominated by the East Asian monsoon, the spatial distribution and temporal characteristics of summer precipitation, such as the diurnal cycle of precipitation and extreme precipitation, are complex and changeable in eastern China. Previous studies have investigated the spatio‐temporal variability of precipitation over eastern China based on observational data and numerical simulations (Ding et al, ; Li et al, ; Liu et al, , ). Shi et al () found that a regional climate model (CREM) could reasonably reproduce the spatial distributions of climatological monthly mean precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation diurnal variations and extremes have received much attention over the last few years. In China, numerous studies have documented the spatial and temporal variation of precipitation diurnal cycle and extreme precipitation (Zhang and Zhai, ; Yu et al, ; Li et al, ; Liu et al, , ). Precipitation frequency and intensity in eastern China, particularly in extreme events, are likely to change within the context of the changing climate.…”
Section: Introductionmentioning
confidence: 99%